PENGARUH CORPORATE GOVERNANCE, KEBIJAKAN HUTANG, NET PROFIT MARGIN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Yang Mengikuti Program Corporate Governance Preception Index CGPI Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014) - Lela Laras Dewi Yanti, 12.05.52.0133; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2017)
This study aimed to determine the effect of corporate governance, debt policy, the net profit margin and the size of the company to the value of the company at the company's corporate governance program preception CGPI index listed on the Indonesia Stock Exchange in 2011-2014. The population is all companies follow corporate governance program preception CGPI index in 2011-2014. The sampling technique in this research is done by using purposive sampling method. Data were analyzed using multiple linear regression analysis. The results of hypothesis testing can be concluded that corporate governance perception index does not affect the value of the company. Debt policy has no effect on the value of the company. Net profit margin positive effect on the value of the company Increased net profit margin will be followed by an increase in the value of the company perusahaan.Ukuran no effect on the value of the company.Keywords: Corporate Governance, Debt Policy, The Net Profit Margin Of Company Size And Value of The Company